2020
DOI: 10.3390/membranes10100257
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Hemoglobin Enzymatic Hydrolysis by a New Ecoefficient Process—Part I: Feasibility of Electrodialysis with Bipolar Membrane and Production of Neokyotorphin (α137-141)

Abstract: Neokyotorphin (α137-141) is recognized as an antimicrobial peptide and a natural meat preservative. It is produced by conventional enzymatic hydrolysis of bovine hemoglobin, a major component of cruor, a by-product of slaughterhouses. However, during conventional hydrolysis, chemical agents are necessary to adjust and regulate the pH of the protein solution and the mineral salt content of the final hydrolysate is consequently high. To produce this peptide of interest without chemical agents and with a low salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…However, the hurdles are still high when dealing with scale-ups and real-life conditions. In their papers, Abou Diab et al [ 5 , 8 ] developed and proposed a new green application of EDBM to the production of bioactive peptides from a by-product of slaughterhouses, which fits perfectly with the concept of a circular economy. Indeed, hemoglobin from blood, once hydrolyzed, allows the bioproduction of active peptides that can then be reused on meat or meat products to increase their preservation and inocuity.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…However, the hurdles are still high when dealing with scale-ups and real-life conditions. In their papers, Abou Diab et al [ 5 , 8 ] developed and proposed a new green application of EDBM to the production of bioactive peptides from a by-product of slaughterhouses, which fits perfectly with the concept of a circular economy. Indeed, hemoglobin from blood, once hydrolyzed, allows the bioproduction of active peptides that can then be reused on meat or meat products to increase their preservation and inocuity.…”
mentioning
confidence: 97%
“…In their papers, Perreault et al [ 1 ], Ge et al [ 3 ], Wang et al [ 4 ], and Abou Diab et al [ 5 ], reported the fouling of membranes by respectively polyphenols and anthocyanins (UF membrane), charged organic anions (anion exchange membranes), and divalent ions (cation exchange membrane), amino acids, and peptide or hem-peptide (cation-exchange membrane). Concerning the mechanisms, the results of the study by Ge et al [ 3 ] indicated that the membrane fouling is caused by two different mechanisms: electrostatic interactions of charged organic anions with the anion exchange membranes and precipitation of Ca 2+ and Mg 2+ on the cation exchange membrane, by reaction with OH − ions generated by water dissociation.…”
mentioning
confidence: 99%
See 3 more Smart Citations